Intervensi Edukasi Tentang Pengasuhan Anak pada 1000 Hari Pertama Kehidupan (HPK) Di Wilayah Puskesmas Takalalla Kabupaten Soppeng - Mappamadeng, Andi Anggreany; Kurnaesih, Een; Idris, Fairus Prihatin (An Idea Health Journal, 2021)
A child needs nurturing, love, and honing as basic needs to achieve optimal growth and development. Not meeting optimal nutrition in 1000 HPK children can have a negative impact on optimal brain growth. If the brain growth is not optimal, the child's cognitive development will be hampered. This can result in reduced intelligence of the baby. The purpose of this study was to analyze the effect of educational interventions on child care in the first 1000 days of life in the Takalalla Health Center area, Kab. Soppeng. The type of research used is Quasi Experiment with a two group pretest and posttest design approach. The sample in this study were mothers who had children aged 0-24 months, totaling 32 people in the intervention group and 32 people in the control group. Data collection through Questionnaire. Data were analyzed using paired T test with 95% confidence interval (CI) and < 0.05. The results showed that the Educational Intervention on Knowledge (p= 0.001), Attitude (p=0.000), Action (p=0.002), and belief (p=0.000) had a significant effect on Parenting in the First 1000 Days of Life, while the most influential is the action of the mother with a coefficient value of = 0.716 and P-Value value of 0.026 <0.05. It is hoped that the provision of more practical information to the community, especially mothers, especially prospective mothers in preparing quality future generations, especially in the first 1000 days of life and further optimizing Posyandu services, and involving the participation of families such as husbands and parents when socializing and providing information is carried out